Archaeomagnetic dating of the baked oven from an extinct medieval settlement in Nededza, near Žilina Town - ORLICKÝ, Oto; BEDNÁR, Peter; DAŇOVÁ, Klaudia; TIRPÁK, Ján (Contributions to Geophysics and Geodesy, 2021)
The samples from the baked oven from the KIA – Nededza area, near Žilina Town were studied by the Thellier method. The derived ancient intensity of the field and that of virtual dipole moment data (VDM) have allowed to determine the age of the baked oven, comparing our data with those presented by Bucha (1975) for the Central Europe. These results have dated the existence of this object during the time of about 12th – 13th century AD. This archaeomagnetic dating has supported a preliminary archaeological assessment that the extinct medieval settlement in the place of todays village Nededza survived in the end of 12 th to the first half of the 14th century AD.